ANALISIS KINERJA SIMPANG BERSINYAL KM. 10 KOTA SORONG PAPUA BARAT DAYA - SABRI, MUH. RIZAL. S; Musvira Febriana Umar (Universitas Muhammadiyah Sorong, 2024)
The signalized intersection is Jl. Basuki Rahmat-Jl. S. Maruni is an intersection that connects the city of Sorong with Aimas district, where since 2022 after the expansion of the Southwest Papua province it has encouraged the economy and population growth. Where facilities in the city of Sorong really need to be improved considering the increasing volume of vehicles. At the intersection of three with the signal Km. 10 The city of Sorong needs to review its performance, both the geometric conditions of the intersection and the traffic lights that work at the intersection. This is due to the high volume of vehicles from year to year passing through this intersection, considering that the intersection is in the middle of the city The analytical method used is calculating intersection performance using the 1997 Indonesian Road Capacity Manual (MKJI). Based on the analysis results for calculating intersection performance for intersection conditions where the level of service at the intersection is at value E. after carrying out simulations of traffic lights and road widening At one arm of the intersection you can see the change in service level to C, due to the decrease in the delay value.